Networks of entrepreneurs driving the Triple Helix: two cases of the Dutch energy system - Claudia Werker; Jolien Ubacht; Andreas Ligtvoet (Triple Helix, 2017)
Entrepreneurs are often envisioned as small private start-up firms operating against all odds. Here, we investigate how in the context of the Triple Helix various entrepreneurs form communities and drive institutional and technological change. To theoretically shape a socialized view of entrepreneurship, we use the Triple Helix approach. Our empirical basis is a highly regulated sector driven by various agents, i.e. the Dutch energy system. As it depends very much on natural gas and relies less on renewables compared to similar countries, we analyse two cases where entrepreneurs drove the uptake of renewable energy sources.
Keywords: 330; Triple Helix; Complexity; Energy system; Entrepreneurs; Technological systems; The Netherlands